Sustaining colombians through the entrepreneurial pipeline – a policy challenge for colombia online (2015)
The Global Entrepreneurship Monitor (GEM) is the largest global study of entrepreneurship. GEM started in 1999 with 10 participating countries and in 2013 covered 70 countries whereas most small and medium Enterprise (SME)-related studies and data collection efforts focus on firms, GEM focuses on the attitudes, activities and characteristics of individuals who participate in the various phases of entrepreneurship. The objectives of the GEM research are to: (1) measure differences in the level of entrepreneurid activity between countries; (2) uncover factors determining the level of entrepreneurid activity; and (3) identify policies that may enhance the level (and quality) of entrepreneurind activity at the national level.